Inspirational Manager / How to build relationships that deliver results - Leary-Joyce Judith (Pearson - Prentice Hall, 2007)
Foreword, Acknowledgements, It's Got to Be Better Than This, What It Makes to be an Inspiration Manager, The Beliefs of an Inspirational Manager, Keep on Learning, Focusing Your Attention, The Inspirational Manager as Coach, Building Inspirational Teams, The Performance Management Process, Making the Most of Delegation, Managing Your Talent, Holding the Though Conversations, Recruiting the Best, Building Recognition Into Your Day, The Leader in Every Manager, Index.